PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY , PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2016) - Luluk Mutmainah, 14.05.52.0079; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the effect of Corporate Social Responsibility (CSR) Disclosure, Profitability and Size of the company to the tax aggressiveness of the Manufacturing Company listed on the Indonesia Stock Exchange. Research data is secondary data in the form of company annual report. While the population in this study is a Manufacturing Company listed on the Indonesia Stock Exchange during the year 2012-2016. The sample selection using purposive sampling method using 126 data from 42 manufacturing sector companies listed in Indonesia Stock Exchange in the period 2014 until 2016. Analytical tools used are descriptive statistical analyst, normality test, classical assumption test, model testing and hypothesis testing. Based on the research that has been done, found the result that Corporate Social Responsibility Disclosure (CSR) has positive effect is not significant to Tax Aggressiveness, Profitability has a significant positive effect to Tax Aggressiveness, and Company Size has positive effect is not significant to Tax Aggressiveness. Keywords: Corporate Social Responsibility, Profitability, Company Size, Tax Aggressiveness